2013
DOI: 10.1093/icvts/ivt457
|View full text |Cite
|
Sign up to set email alerts
|

Understanding coronary artery bypass transit time flow curves: role of bypass graft compliance

Abstract: The study confirmed that the TTFM measured at the proximal end of the coronary bypass could be viewed as a sum of graft capacitive flow and the flow that passes through the distal anastomosis. Graft capacitive flow increases the systolic and decreases the diastolic TTFM when measured at the proximal end of the graft. It explains the higher DF when the TTFM is measured at the distal end of the graft and the increase in the PI at the proximal end when Q decreases. As the influence of graft capacitive flow on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…Repositioning of the heart into anatomical position at the end of surgery will obscure the distal end of the graft. Consequently, TTFM measurement is often performed proximally on right-sided grafts, where PI is usually higher, as the high pressured forward flow from the aorta results in higher systolic peak flows in the proximal segment of a by-pass graft and hence in a bigger difference between maximum flow and minimum flow [ 9 ] , as further explained in the following. In theory, a slightly higher PI may well be expected in grafts anastomosed to the left territory, as the PI is obtained by dividing the difference between maximum and minimum flow by the mean flow: .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repositioning of the heart into anatomical position at the end of surgery will obscure the distal end of the graft. Consequently, TTFM measurement is often performed proximally on right-sided grafts, where PI is usually higher, as the high pressured forward flow from the aorta results in higher systolic peak flows in the proximal segment of a by-pass graft and hence in a bigger difference between maximum flow and minimum flow [ 9 ] , as further explained in the following. In theory, a slightly higher PI may well be expected in grafts anastomosed to the left territory, as the PI is obtained by dividing the difference between maximum and minimum flow by the mean flow: .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound gel was applied to the lumen of the probe so that the graft occupied a minimum of 75% of the lumen. During TTFM measurement, the ultrasound probe was placed as close as possible to the distal anastomosis for the most accurate reading of the flow dynamics across the anastomosis, as previous studies have demonstrated slightly lower %DF and higher PI in the proximal compared to the distal segment of a by-pass graft [ 9 ] . TTFM measurements are routinely measured at a mean systemic blood pressure of 75–85 mmHg to exclude the effects on flow of excessively low or high blood pressure.…”
Section: Methodsmentioning
confidence: 99%
“…We are aware of the fact that other nontechnical factors such as the myocardial temperature, the composition and the temperature of the cardioplegia, and the extension and the resistence of the graft and coronary vascular bed may influence the flow at the anastomosis. To overcome this possible bias we have learned from experience that a minimal value of 15 mL/min is easily obtainable with an optimal anastomosis and is independent from nontechnical factors.…”
Section: Discussionmentioning
confidence: 99%
“…Transit-time ow measurement was performed with VeriQ System (Medi-StimAS, Oslo, Norway) after all anastomoses, ventricle and valves reconstructions were completed, the heart-lung machine was disconnected and hemodynamic parameters became stable (mean arterial pressure xed of 75-85 mmHg) [3,22]. Flow parameters recorded in this study included mean graft ow (Q, ml/min), higher pulsatility index (PI), and diastolic lling (DF, %).…”
Section: Ttfm and Evaluation Criteria For Anastomosis Satisfactorymentioning
confidence: 99%